Effectiveness of Helmet therapy for infants with moderate to severe positional plagiocephaly - Jeongho Kim; Jina Kim; Kyu Young Chae (The Korean Pediatric Society, 2024)
Background The use of helmet treatment for positional plagiocephaly has increased recently; however, its effect is unknown in Korea. Purpose This study aimed to investigate the effectiveness of helmet therapy and identify its influencing factors. Methods Ninety pediatric patients diagnosed with moderate to severe positional plagiocephaly received helmet therapy. Severity of moderate to severe positional plagiocephaly was defined as cranial vault asymmetry (CVA) >10 mm or CVA index (CVAI) >6%. Patients were categorized by age, severity, and daily helmet wear. Multiple regression analysis controlled for factors like sex and prematurity. Treatment success was assessed by comparing pre/post-helmet theray CVA and CVAI, considering normalization or decrease to mild plagiocephaly (CVA ≤10 mm or CVAI ≤6%). Results A total of 90 participants were enrolled (mean age, 5.6±1.6 months; male, 53 [58.9%]). The mean helmet therapy duration was 6.4±2.7 months, while the mean daily wear time was 18.4±2.7 hours. Among the 90 patients, 66 (73.3%) had moderate disease and 24 (26.7%) had severe disease. The mean CVA and CVAI decreased by 6.3±2.7 mm and 4.3%±1.8% after versus before treatment (P<0.001). Treatment was successful in 76 infants (84.4%). The most effective changes in CVA and CVAI were noted in those who began treatment before 9 months of age (6.2±2.5 mm and 5.0%±1.9%, P<0.001), had high compliance (6.2±2.4 mm and 4.9%±1.9%, P<0.001), and had high severity (8.0±2.3 mm and 6.6%±1.7%, P<0.001). Conclusion Starting helmet treatment before 9 months and wearing it over 15 hours daily yielded better outcomes.